Instantaneous global navigation satellite system (GNSS)-based attitude determination for maritime applications - Giorgi, G.; Teunissen, Peter; Gourlay, Tim (IEEE, 2012)
Global Navigation Satellite System (GNSS) is a valuable technology for a large number of maritime applications. Other than providing the absolute positioning service, it aids many demanding applications, such as precise docking, formation of surface craft, autonomous vehicles, sinkage monitoring, etc. GNSS carrier-phase-based algorithms provide high-precision positioning solutions, but an integer number of cycles inherent to the observed signal have to be resolved. A newly developed GNSS carrier-phase ambiguity resolution method is tested. The new method solves for the unknown number of integer cycles by exploiting the known placement of the GNSS antennas aboard the vessel. The a priori information on the antennas baseline separation is employed as a hard constraint. A simplified (linearized) version of the method, suitable for large vessels, is also analyzed. The new method was tested against the most challenging scenario when processing GNSS data: single-frequency, single-epoch, unaided ambiguity resolution. Through different tests, the high performance of the new method is demonstrated: high fixing rate, large robustness, and short time-to-fix after initialization, cycle slips, and/or loss of locks. Considerations about the wide spectra of maritime applications are given, and a specific experiment is carried out to demonstrate the capabilities of the method for navigation in shallow waters.